Disability in under-resourced areas in the Western Cape, South Africa : a descriptive analytical study - Maart, Soraya (Department of Health and Rehabilitation Sciences, 2015)
Disability is a complex construct, and our understanding of it has evolved over the years from a purely medical description to encapsulating the experience of those with disability in the context in which they live. The International Classification of Functioning, Disability and Health (ICF) provides a framework to explore the concept in a biopsychosocial framework taking into account the interaction of a person with a health condition with their environment. The central purpose of this thesis was to explore disability within an under resourced context in order to provide data to service planners to improve the health and well-being of those affected. The exploration of disability involved a cross-sectional survey using instruments based on the ICF framework including the Washington Group Short Set of Questions on Disability, the WHODAS-2, the WHOQOL-BREF and the EQ-5D. The objectives were to establish the prevalence of disability and the description of the impairments, functional limitations and participation restrictions of those identified with disabilities. A total of 950 households were visited in Oudtshoorn (a semi-rural town) and Nyanga (a peri-urban area) and information was gathered on 7336 individuals with a mean age of 30.5 years. The majority of the participants were women. Both areas presented with estimates higher than those from the national census (5.0-6,7%). The urban area of Nyanga presented with a disability prevalence of 13.1% and the semi-rural area of Oudtshoorn with a prevalence of 6.8%. Overall the disability rate was 9.7%. The types of impairment and functional limitations were similar in the two areas, but more severe disability was reported in the semi-rural area, that also had significantly more elderly people. Non-communicable diseases were identified as the major cause of disability in both areas, followed by communicable diseases in Oudtshoorn and unintentional trauma in Nyanga. However, a person was twice as likely to be disabled due to non-communicable disease (Odds Ratio 2.2) when living in Oudtshoorn, and three times more likely to be disabled due to intentional trauma when living in Nyanga (Odds Ratio 0.3). Non-communicable diseases were responsible for the largest number of healthy life years lost. Those living in Nyanga had a higher burden of disability due to their lower quality of life scores as measured by the EQ-5D. Respondents in Nyanga consistently scored higher (worse) on all domains of the WHODAS-2 compared to respondents in Oudtshoorn. Living in Nyanga was associated with a 10% increase in domain scores. However, the pattern of scoring was similar and both areas reported worst functioning for the domains of Getting Around and Life Activities, which are associated with physical mobility. Respondents in Oudtshoorn reported better QoL and HRQoL than those in Nyanga. Functional level predicted the QoL scores, with Nyanga reporting worse functioning. Being employed and married was associated with a higher (better) EQ-5D VAS score, while mobility problems, pain or discomfort and anxiety or depression decreased the score. Transport was the most commonly identified barrier in both areas. Major barriers for those living in Oudtshoorn were Surroundings and Help in the home, whereas Help in the home and Prejudice and discrimination were viewed as the major barriers for respondents in Nyanga. The elderly were the ones most likely to not receive the rehabilitation services that they needed. The conclusions that can be drawn from this research are that context influences the experience of disability, and that disability prevalence alone is an insufficient basis for service planning. Those who experience greater deprivation also have a worse experience of disability. It is therefore essential for South Africa policy makers to view disability through a socio-political lens to ensure the equalisation of opportunities for people with disabilities. Improved quality of life for those living in under-resourced communities should be a priority. Service providers should have a broad range of skills to enable them to address not only the rehabilitation needs of people with disabilities, but also their social needs.